1996
DOI: 10.1021/jp950941b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluorescence Quenching by Stimulated Emission on the Spectral Properties of a Solvent-Sensitive Fluorophore

Abstract: We examined the emission spectra and wavelength-dependent anisotropies of the solvent-sensitive fluorophore 4-(dimethylamino)-4′-cyanostilbene (DCS) under condition of fluorescence quenching by stimulated emission. The sample was illuminated with a train of 10 ps pulses at 285 nm, and a train of stimulating pulses at 570 nm which were delayed by a time t d relative to the excitation. Stimulated emission of DCS was demonstrated to occur by observation of gain in the long-wavelength beam. Illumination on the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…The emission spectra are nearly identical in the absence and presence of light quenching. We recognize that the presence or absence of spectral shifts with light quenching may provide information on the rates of solvent relaxation, and such shifts have been observed [32]. In other studies of light quenching of other fluorophores we showed that the extent of quenching was proportional to the amplitude of the emission spectrum at the quenching wavelength.…”
Section: Steady-state Measurements Of Light Quenchingsupporting
confidence: 52%
“…The emission spectra are nearly identical in the absence and presence of light quenching. We recognize that the presence or absence of spectral shifts with light quenching may provide information on the rates of solvent relaxation, and such shifts have been observed [32]. In other studies of light quenching of other fluorophores we showed that the extent of quenching was proportional to the amplitude of the emission spectrum at the quenching wavelength.…”
Section: Steady-state Measurements Of Light Quenchingsupporting
confidence: 52%
“…26,[39][40][41] This phenomenon, which we call light quenching, has already been applied to fluorescence microscopy. 28,42 In ref 42 the authors describe the use of a modulated signal when the light quenching pulses are at a repetition frequency offset from the excitation pulse rate.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Unless stated otherwise, both beams were vertically polarized. Spatial and temporal overlap was accomplished by maximizing light quenching of Pyridine 2 in methanol, which can be accomplished with 380 and 760 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In order to get full information about the ultrafast dynamics, we here develop the isotropic (54.7°) and anisotropic (parallel and vertical) femtosecond fluorescence depletion methods, where the polarizations of dumping beams with respect to that of pumping beam are selected by rotating a zero-level half-wave plate to obtain isotropic (54.7°) and anisotropic (parallel and vertical) results, respectively. The time-resolved anisotropic decay r(t) was calculated from the decay curves under the condition of parallel polarizations (I || ) and perpendicular polarizations (I ⊥ ) of dumping beam relative to the polarization of pumping beam according to eq 3: 33,35,36 The factor G accounts for the difference in sensitivities for the detection of signal in the perpendicular-and parallelpolarized configurations, where G (G ) I ⊥ /I || , when the excitation is vertically polarized) is estimated about 1.02. The instrument response function is determined according to the 1 + 1′ two photon excited fluorescence method as described before, 10,11,34 in which, the IRF (instrumental response function) up to 90 fs is achieved.…”
Section: Methodsmentioning
confidence: 99%